2014
DOI: 10.1371/journal.pone.0105270
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Benefit in Receiving Concurrent Chemoradiotherapy for Elderly Patients with Inoperable Thoracic Esophageal Squamous Cell Carcinoma?

Abstract: Background and purposeThe benefit of concurrent chemoradiotherapy (CCRT) in elderly patients with inoperable esophageal squamous cell carcinoma (SCC) is controversial. This study aimed to assess the efficiency and safety of CCRT in elderly thoracic esophageal cancer patients.Methods and materialsBetween January 2002 and December 2011, 128 patients aged 65 years or older treated with CCRT or radiotherapy (RT) alone for inoperable thoracic esophageal SCC were analyzed retrospectively (RT alone, n = 55; CCRT, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 26 publications
9
31
1
Order By: Relevance
“…Our results showed that CCRT/RT in elderly patients produced an excellent overall survival, with the 2-and 3-year estimated OS, LRFFS, DMFS and PFS were 43.5%, 60.5%, 79.9% and 34.6%, and 35.2%, 58.5%, 77.8% and 29.4%, respectively and the median OS time was 18.6 months in this study. These results were comparable with or slightly better than previous studies [4,5,9,11,[16][17][18][19], which is in part due to the application VMAT and IMRT for RT.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results showed that CCRT/RT in elderly patients produced an excellent overall survival, with the 2-and 3-year estimated OS, LRFFS, DMFS and PFS were 43.5%, 60.5%, 79.9% and 34.6%, and 35.2%, 58.5%, 77.8% and 29.4%, respectively and the median OS time was 18.6 months in this study. These results were comparable with or slightly better than previous studies [4,5,9,11,[16][17][18][19], which is in part due to the application VMAT and IMRT for RT.…”
Section: Discussionsupporting
confidence: 87%
“…Zhang et al found that acute grade 3-4 hematological toxicity was identified in 36.9% and 14.5% in CCRT and RT alone patients, respectively (p = 0.001). CCRT patients had more grade ≥ 2 esophagitis and pneumonitis than RT alone (52.1% vs. 34.5%, p = 0.005) [5].We also found that patients treated with dCCRT developed significantly more grade ≥ 2 neutropenia and gastrointestinal reactions than patients who received sCCRT and RT alone. However, severe (grade 3 and 4) esophagitis was very rare (<2%) and grade 3-4 hematological toxicity was less than 10% in our study, which might be due to advanced RT technique and optimal treatment plan utilized, furthermore, we use oral capecitabine or S-1 to replaceinfusional fluorouracil in double agents regimes, which was also recommended by NCCN guideline and has been shown to be effective in some previous studies [10][11][12].These results suggested that dCCRT should be given to patients with caution and should be used in highly selected elderly patients.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A better OS but not PFS was observed in the patients treated with docetaxel compared to that in the patients who received fluorouracil or platinum. The median OS of patients treated with docetaxel or fluorouracil was higher than that reported in Zhang's study (docetaxel, did not reach the median OS vs 21 months; fluorouracil, 22 vs 17 months). Zhu et al did a randomized phase 2 trial comparing definitive concurrent chemoradiotherapy with docetaxel plus cisplatin vs 5‐Fluorouracil plus cisplatin in patients with esophageal squamous cell carcinoma and reported no significant differences in overall survival and progression‐free survival between the two groups, but the docetaxel plus cisplatin regimen was associated with more severe hematological toxicities.…”
Section: Discussioncontrasting
confidence: 72%
“…When combined with CRT or RT, the EGFR inhibitor demonstrated a survival benefit for esophageal cancer (11,12). As shown in the present study, when treated with RT alone, the objective response rate was 50% at the completion of treatment and 75% at 1-2 months after treatment (11), with 2 patients achieving CR; the efficacy appeared to be superior to that of RT alone (30), but inferior to the historic record of CRT (31).…”
Section: Discussionsupporting
confidence: 52%